An Analysis of Language Style on The King’s Speech Movie - Dahniar Dahniar; Triana S; Muhammad Taufik (English Literature Studi Program Universitas Islam Makassar, 2023)
This research was conducted to determine and analyse language style on The King’s Speech movie using a sociolinguistics approach with the aims: 1) to describe the type of language style, 2) to identify the function of language style in the movie. This research uses a qualitative method. To obtain data, research was carried out by watching The King’s Speech movie and analysing the types & functions of language style. The researcher also uses Joos’ theory of language style types and Jacobson’s theory of language style functions. The results of research that have been show that the types of language style in The King’s Speech movie have an oratorical/frozen style, there are 5 data, casual style has 6 data, consultative style data has 7 data, then deliberative/formal style has 9 data, and the last the intimate style has 10 data. In addition, there are also 6 functions of language style, namely interpersonal function has 1 data, metalinguistic functions have 3 data, poetic functions have 3 data, emotive functions have 4 data, then rhetorical/directive functions have 4 data, and the last cognitive functions has 8 data. The result shows that there are 37 types of the data from the language style types used and 23 data obtained from the 6 language style functions used. This means that style is prominently proves to be used in communication within family relation and close friend. Then the language style function that appears the most in this film is the cognitive function because it provides a lot of general information.